Afatinib treatment in a large real‐world cohort of nonsmall cell lung cancer patients with common and uncommon epidermal growth factor receptor mutation. Issue 4 (26th October 2021) - Huang, Chi‐Hsien; Ju, Jia‐Shiuan; Chiu, Tzu‐Hsuan; Huang, Allen Chung‐Cheng; Tung, Pi‐Hung; Wang, Chin‐Chou; Liu, Chien‐Ying; Chung, Fu‐Tsai; Fang, Yueh‐Fu; Guo, Yi‐Ke; Kuo, Chih‐Hsi Scott; Yang, Cheng‐Ta
Abstract: The epidermal growth factor receptor tyrosine kinase inhibitor (EGFR‐TKI) afatinib improves survival in nonsmall cell lung cancer (NSCLC) patients with EGFR mutation. We analysed the outcome between EGFR mutation subtypes in a large afatinib‐treated cohort in which 516 EGFR ‐mutated NSCLC patients receiving afatinib as front‐line treatment. EGFR uncommon mutations include exon 20 insertion, de novo T790M of high or low allele frequency (dT790MHAF /dT790MLAF ), non‐T790M compound mutation and others, where EGFR exon 20 insertion and dT790MHAF were defined as type‐I and the rest as type‐II uncommon mutation. Four hundred and sixty‐one (89.3%) and 55 (10.7%) patients were common and uncommon mutation, respectively. Exon 20 insertion and dT790MHAF patients demonstrated a significantly shortened progression‐free survival (PFS) (2.6 and 4.1 months) compared to EGFR common mutation, dT790MLAF and other uncommon mutation patients (15.1, 27.0 and 18.4 months; P = 3 × 10 −8 ). Type‐I uncommon mutation was an independent predictor of PFS (HR 4.46 [95% CI, 2.60‐7.64]; P < .001) and OS (HR 2.56 [95% CI, 1.37‐4.75]; P = .003). EGFR L858R patients demonstrated a significantly higher CNS progression (cause‐specific HR, 3.16; 95% CI 1.24‐8.08; P = .016), and type‐I uncommon mutation patients exhibited a significantly higher systemic progression (cause‐specific HR, 4.95; 95% CI 2.30‐10.60; P = 4.3 × 10 −5 ). Tendencies of higher CNS and lower systemic progression were observed in type‐II uncommon mutation patients. A PFS ≥ 12 months (OR 2.38 [95% CI, 1.18‐4.89]; P = .016) and uncommon EGFR mutation (OR 0.08 [95% CI, 0.01‐0.48]; P = .021) were independent predictors of secondary T790M. Afatinib‐treated NSCLC patients presented an EGFR genotype‐specific pattern of disease progression and outcome. Abstract : What's new? For patients with nonsmall cell lung cancer (NSCLC), epidermal growth factor tyrosine kinase inhibitors (EGFR‐TKIs) can significantly improve survival. EGFG‐TKI effectiveness, however, is compromised by acquired EGFR mutations, especially de novo T790M mutations. Here, the impact of EGFR genotypes on the efficacy of afatinib, a second‐generation EGFR‐TKI, was investigated in a cohort of EGFR ‐mutated NSCLC patients. Afatinib efficacy was associated with T790M allele quantity in patients with de novo T790M mutation. In particular, front‐line afatinib therapy was associated with favourable survival in EGFR ‐mutated patients, whereas resistance was marked by a genotype‐specific pattern of disease progression, with secondary T790M development.